(3GdQHjY GdYQHj (B.. (3KhQGJ de JcJed HYOs (3YdGbGJ GdYQH YHQ GdYUhQ heSJbHdgG HYO KhQGJ GdQHjY GdYQHjs - (3ESeGYjd, eUWai YKeGfs ((3GdbGgQIs (3ecJHI eOHhdjs, 2013)
(3Ef GdJZjjQGJ GdMOjKI HYO KhQGJ GdQHjY GdYQHj gj GdGTO EbdGbG ddOhd GdZQHjI dGfgG KhQGJ MQI hJZjjQGJ GfWdbJ HYjOG Yf GdhUGjG GdZQHjI dPG aef GdeJhbY UMhI YQHjI GSdGejI eY JCcjO JONdGJ ZQHjI dJZjQ hLgI gPg GdKhQGJ dcf eG jOYh Edi GdJaGDd HfLGM gPg Gdbhi GdKhQjI aj GMOGK JZjjQ GdefThO gh GdhYj GdYGdj dbGOI gPg GdKhQGJ hJeJYge HMQjI CcHQ aj GJNGP GdbQGQHYjOG Yf GdhUGjG GdZQHjIs
1 2 4 13
Keywords: (3GdYGde GdYQHjs -- (3JGQjNs -- (3KhQGJs; (3GdYGde GdYQHjs -- (3JGQjNs -- (3GdYUQ GdMOjKs